PENGARUH BAURAN PEMASARAN HIJAU TERHADAP KEPUTUSAN PEMBELIAN: (STUDI PADA MAHASISWA PENGGUNA TUPPERWARE STIE SUTAATMAJA SUBANG DAN MAHASISWA KOLEJ UNIVERSITY ISLAM SELANGOR) - Devy Widya Apriandi; Padya Norma Putri (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2024)
Green marketing is product marketing that aims to meet the needs and desires of consumers without causing any harm to the surrounding environment, both the product itself, the production process and its packaging. In implementing green marketing, four elements of the marketing mix are adopted. The marketing mix as is known has 4P components such as Product, Price, Place and Promotion. According to the green marketing philosophy, every element in the marketing mix must have a green outlook in its marketing. This research examines the influence of the green marketing mix on purchasing decisions for Tupperware products. In this study, researchers used a quantitative approach because they wanted to find the relationship between the Green Marketing Mix (X) and purchasing decisions (Y) for Tupperware products. The data collection technique used in this research was a questionnaire distributed online to Stie Sutaatmadja students & Selangor Islamic University College students. The sampling technique uses non-probability sampling with a sample size of 60 students. This research uses data analysis techniques in this quantitative research using descriptive statistics. The results showed that (1) It can be seen that the green marketing mix of Tupperware products for STIE Sutaatmaja Students & Selangor Islamic University Students has been carried out quite well by Tupperware, (2) It can be seen that purchasing decisions for Tupperware products among STIE Sutaatmaja Students & Selangor Islamic University College Students are quite high for Tupperware products, (3) There is an influence between the green marketing mix on purchasing decisions among Tupperware consumers among STIE Sutaatmaja Students & Selangor Islamic University College Students.